Fluorescence microscope (Cyscope®) for malaria diagnosis in pregnant women in Medani Hospital, Sudan - Malik Elfatih M; Mohammed-Elhassan Ehab B; Haggaz Abd Elrahium D; Hassan Saad El-Din H; Adam Ishag (BMC, 2011)
Abstract Background Accuracy of diagnosis is the core for malaria control. Although microscopy is the gold standard in malaria diagnosis, its reliability is largely dependent on user skill. We compared performance of Cyscope® fluorescence microscope with the Giemsa stained light microscopy for the diagnosis of malaria among pregnant women at Medani Hospital in Central Sudan. The area is characterized by unstable malaria transmission. Methods Socio-demographic characteristics and obstetrics history were gathered using pre-tested questionnaires. Blood samples were collected from febrile pregnant women who were referred as malaria case following initial diagnosis by general microscopist. Results During the study period 128 febrile pregnant women presented at the hospital. Among them, Plasmodium falciparum malaria was detected in 82 (64.1%) and 80 (62.5%) by the Giemsa-stained light microscopy and the Cyscope® fluorescence microscope, respectively. The sensitivity of the Cyscope® fluorescence microscope was 97.6% (95% CI: 92.2%-99.6%). Out of 46 which were negative by Giemsa-stained light microscopy, 5 were positive by the Cyscope® fluorescence microscope. This is translated in specificity of 89.1% (95% CI: 77.5%-95.9%). The positive and negative predictive value of Cyscope® fluorescence microscope was 94.1% (95% CI: 87.4% -97.8%) and 95.3% (95% CI: 85.4% - 99.2%), respectively. Conclusion This study has shown that Cyscope® fluorescence microscope is a reliable diagnostic, sensitive and specific in diagnosing P. falciparum malaria among pregnant women in this setting. Further studies are needed to determine effectiveness in diagnosing other Plasmodium species and to compare it with other diagnostic tools e.g. rapid diagnostic tests and PCR.